Determinants of E-commerce Adoption on Business Performance: A Study of MSMEs in Malang City, Indonesia - Abu Muna Almaududi Ausat; Tepi Peirisal (Jurnal Optimasi Sistem Industri, 2021)
This study aims to identify and analyze the impact of e-commerce adoption on the performance of micro, small and medium enterprises (MSMEs). The TOE model framework is used, but the individual context is added as a criticism of the framework as an influential factor in e-commerce adoption. Six intriguing variables were examined with five hypotheses. The questionnaires were distributed to 191 MSMEs in the food and beverage industry using Google forms and sent via WhatsApp application in order to derive their opinions or assessments, which were used as the data collection method in this study. In this study, structural equation modeling-partial least squares (SEM-PLS) was used as an analytical tool. The results of the study show that there is a significant relationship between technology, organizations, and individuals and the variable e-commerce adoption, which is expected to have a significant impact on MSME performance. MSMEs should be better able to take advantage of the opportunities presented by the business environment to improve their performance through the use of e-commerce. As a result, MSME owners are advised to use explicit competitive strategies through various activities carried out by the functional departments of the organization, such as emphasizing their advantages or expertise. In addition, the government must continue to take steps to improve human resource skills in e-commerce through various coaching, competency, and training opportunities.